Reinterpreting Religious Pluralism in QS. al-Baqarah: 62 (A Method of al-Qaraḍâwî’s Interpretation) - Muhammad Kudhori; Muhammad Faiq; Ibnu Farhan (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2021)
QS. al-Baqarah: 62 by some Muslim scholars is used to justify that adherents of all religions in this world will get salvation and go to paradise. Salvation in the hereafter, according to them, is not required to believe in the Prophet Muhammad. This article aimed to re-examine that interpretation that is contrary to the belief of the majority of Muslims, in which one aspect of faith that will save people is a belief in the messengers, including a belief in the Prophet Muhammad. The reinterpretation of QS. al-Baqarah: 62 in this study employed the interpretation method of Yûsuf al-Qaraḍâwî in his book entitled Kayfa Nata‘âmal Ma‘ al-Qur’ân al-‘Azîm. This article is a library based-study by using content analysis and descriptive-analytic. The result revealed that QS. al-Baqarah: 62 actually deals with the earlier peoples before the Prophet Muhammad. Those who believe in Allah and the Last Day and do good deeds are promised a reward from Allah SWT